New perspectives on modern Wales studies in Welsh language, literature and social politics - Asmus, Sabine; Jaworska-Biskup, Katarzyna (Cambridge Scholars Publishing, 2019)
This book discusses issues of Welsh literature, history and the vernacular language of the devolved region of Wales (as a part of the United Kingdom of Northern Ireland and Great Britain). In this context, the volume sheds light on various aspects of the identity construction of a small nation with an endangered language, which is a P-Celtic tongue, known for exhibiting many features alien to Indo-European and SAE languages. All the issues tackled here are presented in diachronic and synchronic perspective, allowing for correlations to be drawn with similar problems faced by other cultures.As.